A theoretical study on the structural and physical properties of the ground-state CaC. (February 2015) - Qian, Yan; Wu, Haiping; Kan, Erjun; Lu, Ruifeng; Tan, Weishi; Deng, Kaiming
Abstract: Because of no experimental report on the half-metallic CaC theoretically found by Gao et al. in 2007, it is necessary to explore the nature of this fact, and the reason is revealed via density-functional theory study in this work. By a particle swarm structural search firstly, several CaC allotropes are found, including the half-metallic one with F- 43 m space group. Among the found compounds, six allotropes have the negative formation energies with Ccma, P 4/ mmm, Immm, Cm (8), Pmm 2, and Cmmm space groups while the half-metallic one has positive formation energy of 2.67 eV. Furthermore, through the study on the dynamical properties of these six thermally stable CaC allotropes, only the one with P 4/ mmm symmetry exhibits dynamical stability. Based on the above fact, CaC with P 4/ mmm symmetry, instead of the F- 43 m one, perhaps can be experimentally synthesized due to both the thermodynamic and dynamically stabilities. Highlights: Several CaC structures were found by CALYPSO code. The stable CaC with both thermodynamically and dynamically stabilities shows P4/mmm space group. The stable CaC exhibits metallic nature, instead of half-metallic character.